Efficient electrochemical reduction of CO to C2 products on the transition metal and boron co-doped black phosphorene - Kong, Lingyi; Chen, Zhe; Cai, Qinghai; Yin, Lichang; Zhao, Jingxiang (Chinese chemical letters, 2022)
The synthesis of high-value multi-carbon products through the electrochemical reduction of carbon monoxide (COER) is one of the promising avenues for carbon utilization and energy storage, in which searching for efficient electrocatalysts that exhibit moderate CO intermediate binding strength and low kinetic barrier for C-C coupling is a key issue. Herein, by means of comprehensive density functional theory (DFT) computations, we theoretically designed three synergistic coupling catalysts by co-doping transition metal (TM = Fe, Co and Ni) and boron (B) into the two-dimensional black phosphorene (BP), namely TM-B@BP for COER to C2 products. DFT computations and ab initio molecular dynamics simulations reveal the good stability and high feasibility of these proposed TM-B@BP catalysts for practical applications and future experimental synthesis. More interestingly, high-value ethylene (C2H4), ethane (C2H6) and ethanol (C2H5OH) products can be obtained on these three designed electrocatalysts with ultra-small limiting potentials (−0.20∼−0.41 V) and low kinetic energy barriers of C-C coupling (0.52∼0.91 eV). Meanwhile, the competitive one-carbon (C1) products and hydrogen evolution reaction can also be effectively suppressed. The promising activity and selectivity of these three designed electrocatalysts render them ideal candidates for CO electroreduction, thus providing a cost-effective opportunity to achieve a sustainable production of high value C2 chemicals and fuels. [Display omitted] As-designed three synergistic coupling electrocatalysts based on 2D black phosphorene for reducing CO to high value-added multi-carbon products.